Early Miocene volcanic activity and paleoenvironment conditions recorded in tephra layers of the AND-2A core (southern McMurdo Sound, Antarctica) - Di Roberto A.; Del Carlo P.; Panter K. S.; ROCCHI, SERGIO (Geosphere, 2012)
The ANtarctic geological DRILLing Program (ANDRILL) successfully recovered 1138.54 m of core from drill hole AND-2A in the Ross Sea sediments (Antarctica). The core is composed of terrigenous claystones, siltstones, sandstones, conglomerates, breccias, and diamictites with abundant volcanic material. We present sedimentological, morphoscopic, petrographic, and geochemical data on pyroclasts recovered from core AND-2A that provide insights on eruption styles, volcanic sources, and environments of deposition. One pyroclastic fall deposit, 12 resedimented volcaniclastic deposits and 14 volcanogenic sedimentary deposits record a history of intense explosive volcanic activity in southern Victoria Land during the Early Miocene. Tephra were ejected during Subplinian and Plinian eruptions fed by trachytic to rhyolitic magmas and during Strombolian to Hawaiian eruptions fed by basaltic to mugearitic magmas in submarine and/or subglacial to subaerial environments. The long-lived Mount Morning eruptive center, located ~80 km south of the drill site, was recognized as the probable volcanic source for these products on the basis of volcanological, geochemical, and age constraints. The study of tephra in the AND-2A core provides important paleoenvironment information by revealing that the deposition of primary and moderately reworked tephra occurred in a proglacial setting under generally open-water marine conditions.